The impacts of human land-use change on avian diversity and associated ecosystem functions - Bregman, T; Tom Porter Bregman (2014)
Understanding the impacts of land-use change on biodiversity and the ecosystem services that it provides is of great importance given unprecedented growth of the human population. Past studies attempting to explore these impacts have described the overall structure of communities (i.e. species richness and trait diversity) across gradients of local scale degradation and fragmentation, and have sought to identify whether the loss of species following land-use change is non-random. Yet, despite a wealth of research we still lack a generalised understanding of how land-use change impacts on traits responsible for determining species sensitivity and their role within ecosystems, particularly for vertebrates. Moreover, despite the importance of niche-based processes in the assembly of communities, we have not yet elucidated whether these are important in mediating the collapse of communities in human-dominated landscapes. To fill these existing research gaps, I collated comprehensive avian species inventories from fragmented and degraded forests and compared their structure with communities existing in continuous forests. In Chapter 2, I tested whether sensitivity of species to forest fragmentation varies between the temperate zone and the tropics and whether there are key differences in the size of fragments required to maintain ecosystem processes in these regions. I found that sensitivity to fragmentation varies according to functional group and body mass, with the prevalence of insectivores and large frugivores declining in relation to fragment size, particularly in tropical fragments smaller than 100 ha. In Chapter 3, I tested whether functional diversity and the mean position of trait diversity of insectivores and frugivores, changed across a gradient of intensifying land-use change. I found a decline in the functional diversity of forest species and a shift in the mean community traits for both forest and non-forest species. In Chapter 4, I tested whether the structure of tropical bird communities are influenced by species interactions in a fragmented landscape. I found increasing over-dispersion in functional and phylogenetic trait relatedness among species with decreasing fragment size, suggesting that competitive interactions are important in the disassembly of avian communities. In Chapter 5, I modelled the impact of forest cover change on ecosystem function across the Brazilian Amazon, focusing on seed dispersal by birds. Furthermore, I tested whether ecosystem function declined linearly with decreased forest cover after accounting for differences in the underlying pools of species. I found the lowest levels of functional diversity along the southern arc of deforestation and that the dispersal of large seeds showed some resilience to declining forest cover. Taken together, my results suggest that the loss of species from communities in degraded and fragmented landscapes is strongly non-random. Insectivores and large frugivores are most sensitive to land-use change, with species located in the densest parts of trait space being most threatened by a decline in forest patch size, suggesting that species interactions regulate the collapse of avian diversity in human-modified forests. I conclude that land-use change has important implications for the provisioning of ecosystem services, including seed dispersal and the control of insect herbivores. The impact of future land-use change is likely to be mediated by the composition of the original pool of species and the amount of redundancy in the ecosystem services that they provide. I discuss the relevance of my findings to land-use management strategies and policy interventions, and in particular conclude that these should, where possible, maintain pristine forest patches above 1000 ha, improve connectivity among habitat patches, and ensure greater protection for logged and burnt forests. Future studies should focus on clarifying the link between shifts in vertebrate community structure and the functioning of forest ecosystems.